The Integration of Education and Public Health in Enhancing Adolescents’ Awareness of Tuberculosis - La Ode Asrianto; Teti Susliyanti Hasiu; Sarifudin Andi Latif; Budi Prasetyo (Jurnal Wawasan Sarjana, 2025)
Tuberculosis (TB) remains a major global public health problem, particularly in developing countries, including Indonesia. Adolescents are a vulnerable group that often lacks adequate awareness and understanding of TB prevention. Therefore, integrating education and public health approaches is considered a strategic effort to improve adolescents’ awareness. This study aims to examine the effectiveness of integrating education and public health in enhancing adolescents’ awareness of tuberculosis. The research employed a quantitative approach with a quasi-experimental design using a non-equivalent control group design. Data were collected through questionnaires administered as pre-test and post-test to both experimental and control groups. The data were analyzed using descriptive statistics and inferential tests, including paired sample t-test and independent sample t-test. The results showed a significant increase in adolescents’ awareness in the experimental group, with the mean score rising from 62.45 to 81.30, while the control group showed only a slight increase. Statistical analysis indicated a significant difference between the two groups (p < 0.05). The findings suggest that the integration of education and public health is effective in improving adolescents’ knowledge, attitudes, and preventive behaviors toward TB. In conclusion, this integrated approach can be used as an effective strategy for TB prevention among adolescents.